Perancangan Sistem Donasi Berbasis Web (Sudi Kasus : Desa Parung Panjang) - Wawa Wiwaha; Dena Wulandari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Parungpanjang village is one of the service providers in the village, both in the fields of government, empowerment, development or guidance, which is centered in the village office. The existence of a village office can reflect the identity of the village itself. Because of this, it would not be wrong if the village government to program a program that is beneficial to many people, especially for the village itself. In parungpanjang village, there is a social assistance program that is still offline, where the process or program activities are carried out only at the village office. By utilizing existing information technology advances, thereby increasing the ease and wider reach of information for donors who want to provide assistance anywhere and anytime. In this study, the author uses a web-based application using the rapid application development method, php programming language, and data storage using mysql. With this web-based donation information system, it helps donors and village employees in making donations and can improve and improve services to the general public, especially residents of Parungpanjang village.